Mechanisms of cisplatin-induced cell death in malignant mesothelioma cells: Role of inhibitor of apoptosis proteins (IAPs) and caspases - Cregan, I.; Dharmarajan, Arunasalam; Fox, S. (Spandidos Publications, 2013)
Malignant mesothelioma (MM) is an aggressive and highly chemoresistant tumour. Although cisplatin is used in frontline therapy of this disease treatment remains palliative at best. The biochemical pathways activated by cisplatin and the mechanisms of resistance in mesothelioma cells are poorly understood. Overexpression of inhibitor of apoptosis proteins (IAPs) has been described in clinical mesothelioma tumours and proposed as therapeutic targets. In this study, we examined cisplatin-induced cell death pathways and IAPs in three mesothelioma-derived cell lines. Cisplatin induced cell death in mesothelioma cell lines was characterised by biochemical mechanisms classically associated with apoptosis including: mitochondrial depolarisation, phosphatidylserine translocation and caspase activation. Surprisingly mRNA expression of IAPs in mesothelioma was not upregulated relative to primary mesothelial cells except for survivin which was higher in the most resistant cell line. In contrast, protein expression of both XIAP and survivin was upregulated in all mesothelioma cells, consistent with post-translational regulation. Knockdown of either XIAP or survivin by RNAi did not affect the sensitivity to cisplatin in any of the cell lines. Survivin RNAi did, however, inhibit proliferation in the highest expressing cell line, ONE58. The pan-caspase inhibitor z-VAD and the more selective caspase 3/7 inhibitor z-DEVD had no effect upon the sensitivity of any of the cell lines to cisplatin indicating that caspase-independent pathways predominate. The findings of the present study provide insights into cisplatin-induced mechanisms in mesothelioma cells and show that alternative pathways are operating which may provide new options for targeting this extremely resistant tumour.